Epoxy‐rich Fe Single Atom Sites Boost Oxygen Reduction Electrocatalysis - Zhao, Yufei; Shen, Ziyan; Huo, Juanjuan; Cao, Xianjun; Ou, Pengfei; Qu, Junpeng; Nie, Xinming; Zhang, Jinqiang; Wu, Minghong; Wang, Guoxiu; Liu, Hao (Angewandte Chemie International Edition, 2023)
Electrocatalysts for highly efficient oxygen reduction reaction (ORR) are crucial for energy conversion and storage devices. Single‐atom catalysts with maximized metal utilization and altered electronic structure are the most promising alternatives to replace current benchmark precious metals. However, the atomic level understanding of the functional role for each species at the anchoring sites is still unclear and poorly elucidated. Herein, we report Fe single atom catalysts with the sulfur and oxygen functional groups near the atomically dispersed metal centers (Fe1/NSOC) for highly efficient ORR. The Fe1/NSOC delivers a half‐wave potential of 0.92 V vs. RHE, which is much better than those of commercial Pt/C (0.88 V), Fe single atoms on N‐doped carbon (Fe1/NC, 0.89 V) and most reported nonprecious metal catalysts. The spectroscopic measurements reveal that the presence of sulfur group induces the formation of epoxy groups near the FeN4S2 centers, which not only modulate the electronic structure of Fe single atoms but also participate the catalytic process to improve the kinetics. The density functional theory calculations demonstrate the existence of sulfur and epoxy group engineer the charges of Fe reactive center and facilitate the reductive release of OH* (rate‐limiting step), thus boosting the overall oxygen reduction efficiency. Fe single atom catalysts with sulfur and epoxy groups near the atomically dispersed metal centers (Fe1/NSOC) are designed for highly efficient oxygen reduction reactions. The presence of sulfur and epoxy groups modulates the electronic structure of Fe centers, while the epoxy groups also participate in the reduction reaction through reversible cleavage, lowering the energy barrier by functioning as an anchor site for OH* intermediates.